Influence of upper- and lower-body sports compression garments on markers of cross-country ski performance - Heil, D.; Mclaren, J. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The present study sought to evaluate the effects of wearing a custom-designed full-length two-piece compression ski uniform on markers of roller skiing economy, blood lactate, and upper-body power (UBP) in trained crosscountry skiers. The effects of wearing the compression garment uniform were compared directly to the effects of the same skiers wearing their own noncompression ski racing uniform. The compression garments were part of a multi-phase project to design a unique two-piece garment uniform that complimented the kinematic movements of cross-country skiers.